The Role of Postmodern Consumers’ Materialistic Tendencies and Brand Attitudes on Fashion Product Buying Decisions - Özmen, Alparslan; Kuş Tekin, Sümeyye (Journal of Applied And Theoretical Social Sciences, 2023)
Nowadays, technology and social environment are changing rapidly due to globalization. Production and consumption have also changed with technological developments. Consumers exhibit different behaviors during this period. Therefore, postmodern society has turned into a consumption-oriented society emerged as a reaction to modern society. In postmodernism, consumption activities refer to a meaning different than meeting individuals’ needs. Goods are mostly preferred due to their symbolic values. Postmodern consumers are people who reinvent themselves through consumption and develop individualized identities through exciting consumption experiences. Additionally, they try to be seen as socially powerful by presenting themself in front of other consumers through brands. Therefore, this research attempts to investigate the effect of brand attitude and materialistic tendencies on postmodern consumers' decision to purchase fashion products. Accordingly, data were collected through online survey from 388 participants living in Manisa using convenience sampling method. Four scales were used in the research. The hypotheses are tested with the SPSS 21 statistical program. The reliability of the scales was tested with Cronbach's Alpha coefficient. Then, Kolmogorov-Smirnov test, frequency analysis, correlation and regression analysis were performed. According to the obtained results, the model is meaningful as a whole. The findings reveal that consumer characteristics and brand attitudes have a positive effect on consumers' decision to purchase fashion products. In addition, brand attitude has a greater impact on the purchasing decision than postmodern consumer characteristics. As a result, businesses need to address all these matters.